Individual, Household, and Community Drivers of Dengue Virus Infection Risk in Kamphaeng Phet Province, Thailand - Gabriel Ribeiro dos Santos; Darunee Buddhari; Sopon Iamsirithaworn; Direk Khampaen; Alongkot Ponlawat; Thanyalak Fansiri; Aaron Farmer; Stefan Fernandez; Stephen J. Thomas; Isabel Rodríguez-Barraquer; Anon Srikiatkhachorn; Angkana T. Huang; et al. (The Journal of Infectious Diseases, 2022)
BACKGROUND: Dengue virus (DENV) often circulates endemically. In such settings with high levels of transmission, it remains unclear whether there are risk factors that alter individual infection risk. METHODS: We tested blood taken from individuals living in multigenerational households in Kamphaeng Phet province, Thailand for DENV antibodies (N = 2364, mean age 31 years). Seropositivity ranged from 45.4% among those 1-5 years old to 99.5% for those >30 years. Using spatially explicit catalytic models, we estimated that 11.8% of the susceptible population gets infected annually. RESULTS: We found that 37.5% of the variance in seropositivity was explained by unmeasured household-level effects with only 4.2% explained by spatial differences between households. The serostatus of individuals from the same household remained significantly correlated even when separated by up to 15 years in age. CONCLUSIONS: These findings show that despite highly endemic transmission, persistent differences in infection risk exist across households, the reasons for which remain unclear.
Keywords: Mosquito-borne diseases and control; Viral Infections and Outbreaks Research; Malaria Research and Control